Formation of an unusual bis(diguanidinate) ligand via nucleophilic attack of a guanidinate onto a carbodiimide - Melen, Rebecca L.; Simmonds, Hayley R.; Wadepohl, Hubert; Wood, Paul T.; Gade, Lutz H.; Wright, Dominic S. (Australian journal of chemistry, 2014)
During an investigation of the synthesis of the new mono- and bis(guanidinate) complexes [{iPr2NC(···NiPr)2}GaCl2] (2) and [{iPr2NC(···NiPr)2}2GaCl] (3) from the in situ reactions of the lithium guanidinate [{iPr2NC(···NiPr)2}Li]n (1) with GaCl3, an unexpected new guanidinate expansion reaction was uncovered in which it is found that the nucleophilic addition of 2 to the carbodiimide, iPrN=C=NiPr, gives [iPrN{C(NiPr)=NiPr}{C(=NiPr)NiPr2}GaCl2] (4), containing an unusual bis(diguanidinate) ligand.
Gesehen am 25.09.2020